2009
DOI: 10.1016/j.chembiol.2009.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Differential Presentation of Protein Interaction Surfaces on the Androgen Receptor Defines the Pharmacological Actions of Bound Ligands

Abstract: Summary The pharmacological activity of different nuclear receptor (NR) ligands is reflected by their impact on receptor structure. Thus, we asked whether differential presentation of protein-protein interaction surfaces on the androgen receptor (AR), a surrogate assay of receptor conformation, could be used in a prospective manner to define the pharmacological activity of bound ligands. To this end, we identified over 150 proteins/polypeptides whose ability to interact with AR is influenced in a differential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 52 publications
2
49
0
Order By: Relevance
“…HepG2 cells were maintained in Basal Medium Eagle (Sigma Aldrich) containing 8% FBS. For mammalian 2-hybrid-based AR cofactor assays (41,42), cells were seeded in 96-well plates and transfected with VP16-AR (900 ng), 5XGalLuc3 (900 ng), Gal4-interactor (900 ng), and Renilla-Luc (300 ng) using Lipofectin (Thermo Fisher Scientific). Cells were then treated with the ligands as indicated in Figure legend 3 for 48 hours, at which point, dual-luciferase assays were performed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…HepG2 cells were maintained in Basal Medium Eagle (Sigma Aldrich) containing 8% FBS. For mammalian 2-hybrid-based AR cofactor assays (41,42), cells were seeded in 96-well plates and transfected with VP16-AR (900 ng), 5XGalLuc3 (900 ng), Gal4-interactor (900 ng), and Renilla-Luc (300 ng) using Lipofectin (Thermo Fisher Scientific). Cells were then treated with the ligands as indicated in Figure legend 3 for 48 hours, at which point, dual-luciferase assays were performed.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we reported on the development and validation of a cell-based AR conformationprofiling tool that utilizes peptide probes derived from nuclear receptor coregulators to survey ligand-induced alterations on the surface of the receptor (41,42). This tool leverages the observation that receptor conformation, a primary determinant of coregulator recruitment, is predictive of the pharmacological activity of AR ligands.…”
Section: Cyp17 Inhibitors Directly Bind and Antagonize Ar Activitymentioning
confidence: 99%
“…In fact, improved therapy of CRPC could result from targeting cellular factors that control AR activity (Nabhan et al 2011). Although the role of the AR in prostate health and disease has been illuminated by highthroughput genomic Sharma et al 2013), metabolomic (Sreekumar et al 2009), and chemical-biology approaches (Norris et al 2009), systematic profiling of the genes that functionally regulate AR action has not been conducted.…”
Section: New York New York 10016 Usamentioning
confidence: 99%
“…The failure of hormonal therapy for prostate cancer has been largely attributed to overexpression of AR in recurrence of the cancer (Chi et al, 2009;Joseph et al, 2009;Norris et al, 2009;Singh et al, 2008;Tran et al, 2009;Zhou et al, 2008). Development of more effective hormonal therapeutic agents targeting overexpressed AR becomes an important research area.…”
Section: Overexpressed Ar and Ar Variants In Crpc As Therapeutic Targetsmentioning
confidence: 99%
“…Many AR antagonists previously developed are mainly ligand competitors for androgens and can not overcome the over-expressed AR in CRPC. Newer approaches have been used to develop agents that can target potential sites in the AR to abrogate the function of the mutated or over-expressed receptor in cancer cells (Chi et al, 2009;Joseph et al, 2009;Norris et al, 2009;Singh et al, 2008;Tran et al, 2009;Zhou et al, 2008;Shen & Balk, 2009). For example, it was reported that a conformation-based assay was used to screen a diverse small molecule library of ≈10,000 compounds in order to select chemicals that can inhibit the AR-gelsolin interaction .…”
Section: Overexpressed Ar and Ar Variants In Crpc As Therapeutic Targetsmentioning
confidence: 99%